Virtual solar system / Chong Yee Wah - Chong, Yee Wah (2004)
3D modelling is a three-stage process: First, obtain data and get it into computer; second, use the computer to interact with it, just as manipulating real object, but without annoyances like gravity and material strength· and third. output or store the modified data. Or, the data might subsequently be made 'real' again by automatically fabricating an object using. Deriving a solar system is much challenging as it involves creation of nine different sizes of planets, obtaining the images that can be combined to form a realistic 30 meshes, importing the sound files that can pronounce the name of the planets and provide physically-valid movements for the planets. In this Virtual Solar System's project, the goal is to create the interest for the younger generation especially in the primary school the existing of Virtual Reality world and to provide some basic information pertaining all the planets. The methods used to create this animated JD-model of the Solar System are as follows: - • Data Acquisition - This includes obtaining colour-textured image. of all the nine planets as well as recording and editing the pronunciation of each planet. • Building the 30 model - This include creation of various size for all the planets. • Colour - Texture Mapping- This includes setting and properly aligning the 2D textured data onto the 3D model. • Animation This includes creating of revolving movement for the planets around the Sun.